The Use of Social Media Tik Tok in Character-Based Indonesian Language Learning - Siva Hidayatul Qirom; Retno Winarni; Eka Budhi Santosa (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This literature review is motivated by the rapid development of digital technology and the increasingly widespread use of social media among students, especially TikTok social media, which has presented opportunities as well as challenges in the world of education, especially in learning Indonesian in elementary schools based on instilling character values. This study aims to evaluate the results of research related to the use of TikTok in supporting Indonesian language learning and shaping students' character. The study method used is a literature review of various scientific articles in the last five years that discuss the relationship between TikTok use, learning motivation, language skills, and student character.  The results of the study show that TikTok can increase students' motivation, learning engagement, and speaking skills, as well as foster character values such as self-confidence, social awareness, and creativity. However, the findings also indicate that without proper supervision, the use of TikTok can have negative impacts such as the use of non-standard language and decreased polite behavior. Therefore, a planned pedagogical strategy is needed as well as the active role of teachers and parents in filtering and interpreting the content consumed and produced by students. In conclusion, TikTok has the potential to be an innovative learning media that supports language literacy and character building if used wisely and educatively.